2017
DOI: 10.17957/ijab/15.0279
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Relationship and Diversity among Chinese Sugarcane Parental Clones using SCoT and ISSR Markers

Abstract: Sugarcane is an allopolyploid crop with ≥120 or more chromosomes, of which~5.0-10% are Saccharum spontaneum and 90-95% are S. officinarum. The genetic characteristics of sugarcane provides a complex genetic background. The objective of this study was to use two molecular marker systems, start codon targeted (SCoT) and inter-simple sequence repeat (ISSR), to assess the genetic relationship and diversity of 75 sugarcane parental clones from Chinese sugarcane breeding program. Twenty-four SCoT primers produced 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Many study also reported that in many sugarcane crossing program around the world, the parents that used for crosses originated from inter-and intraspecific hybridization and its progenies. They results progenies with the same and share genetic makeup with parents (Stevenson, 1965;Zhang et al, 2001;Perera et al, 2012;Filho et al, 2010;Pan et al, 2003;Hapsoro et al, 2015;Chen et al, 2017). In contrast to previous result, in crosses between Erianthus sp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Many study also reported that in many sugarcane crossing program around the world, the parents that used for crosses originated from inter-and intraspecific hybridization and its progenies. They results progenies with the same and share genetic makeup with parents (Stevenson, 1965;Zhang et al, 2001;Perera et al, 2012;Filho et al, 2010;Pan et al, 2003;Hapsoro et al, 2015;Chen et al, 2017). In contrast to previous result, in crosses between Erianthus sp.…”
Section: Discussionmentioning
confidence: 88%
“…This term based on the appearance of progenies at the early stage of selection (Sukarso, 1986in Budhisantoso, 2012. Therfore, the choice of parents and parents set is the crucial aspect in sugarcane breeding programe (Skinner, 1971in Budhisantoso, 2012Hapsoro et al, 2015;Chen et al, 2017). The choice of pricise parents and parents set will determine the success of the crossing by the appearance of progenies better than the average or the best parent value (heterosis).…”
Section: Discussionmentioning
confidence: 99%
“…The SCoT primers that generated polymorphic fragments in two bulk pools were first screened using the established SCoT-PCR (Chen et al 2017). Then, further testing of the selected primers using 10 lines (individuals in pools) was performed, and 34 control cultivars were assessed for primer polymorphisms and the specific fragment was obtained that was amplified only in the smut-resistant or susceptible materials.…”
Section: Scot Primer Screening and Validationmentioning
confidence: 99%
“…The identification of smut resistance is an important part of sugarcane breeding, and the traditional identification method of sugarcane smut resistance involves phenotypic identification by artificial inoculation. However, this method is generally time and energy consuming, and it is difficult to evaluate disease resistance of the sample on a large scale, and the identification results are also affected by environmental interaction effects (Chen et al 2017). Marker assisted selection (MAS) is not affected by genotype and environment interactions and can significantly improve the selection efficiency and accuracy of disease-resistant breeding when combined with routine identification methods, although selection accuracy requires molecular markers that are closely linked to target traits (Lee 1995;Collard and Mackill 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation